2001
DOI: 10.1525/rac.2001.11.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Of Markets and Missions: The Early History of the Universal Fellowship of Metropolitan Community Churches

Abstract: “It seems to me, now,” reflected Troy Perry, four years after founding a successful new Protestant denomination, “that it must have been a matter of timing, and I think that it was fate, too! God chose me for my mission at a time when He knew the world would respond, once the need was made clear.” While the question of divine ordination is a bit outside the scholar's jurisdiction, the question of timing is a crucial one for historical inquiry, and Perry's remarks show an insightful awareness that the success o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
0
13
0
3
Order By: Relevance
“…Echoing homonormative assertions originally promoted by LG churches in the 1960s (Wilcox ), respondents suggested that people who could not help being different might be okay, which also suggested anyone who could would (and perhaps should) choose to be heterosexual (Warner ). In so doing, they tolerated LGB existence by framing it as an uncontrollable defect from heterosexual nature or supremacy (Schrock, Sumerau, and Ueno ).…”
Section: Strategies Of Conditional Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…Echoing homonormative assertions originally promoted by LG churches in the 1960s (Wilcox ), respondents suggested that people who could not help being different might be okay, which also suggested anyone who could would (and perhaps should) choose to be heterosexual (Warner ). In so doing, they tolerated LGB existence by framing it as an uncontrollable defect from heterosexual nature or supremacy (Schrock, Sumerau, and Ueno ).…”
Section: Strategies Of Conditional Acceptancementioning
confidence: 99%
“…Studying the ways that people construct religion, gender, and sexuality, then, has the potential to yield insight into the processes that uphold large-scale patterns of inequality (McQueeney 2009). At the same time, we can learn about social change by attending to the ways people challenge and/or reproduce inequalities (Wilcox 2001).…”
mentioning
confidence: 99%
“…In 1943, Quakers issued the first official denominational statement concerning the “problem” of homosexuality in American society (Wilcox ). Since then, homosexuality has become a prominent issue in American Christianity.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our analysis reveals that LDS elites utilized these same narrative devices before the emergence of these other groups in the mid‐to‐late 1970s. While we are not able to explicate what, if any, influence LDS elites had on the emergence of these other—more well‐known—movements, the historical record suggests that they could have done so, that they also could have later been influenced by the emergence of these groups, and that the most likely source of inspiration for LDS elites would have been the statements on homosexuality in the 1940s and 1950s by the Quaker and Catholic traditions, which initially conceptualized it as a problem or disorder that afflicted otherwise moral people (see Wilcox for a concise review of these statements). Regardless of the direction of influence, we thus utilize the LDS historical record to illustrate generic patterns of inequality reproduction that continue to influence social, political, religious, and sexual debates today.…”
Section: Methods and Analysismentioning
confidence: 86%
“…Over the past 70 years, religious leaders have wrestled with the emergence of homosexuality in the public sphere (see Wilcox ). While some religious organizations have begun to open their doors to nonheterosexuals (McQueeney ; Moon ) and some groups of sexual minorities have founded their own religious institutions (Sumerau ; Thumma ), other religious groups have responded with fierce opposition (see e.g., Erzen ; Pitt ; Robinson and Spivey ).…”
Section: Mormonism and Homosexualitymentioning
confidence: 99%